KAJIAN HUMOR DALAM RUBRIK SEMARANGAN DJAKA LODANG - Herlina Setyowati (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2018)
Abstract: The aim of creating humor is to entertain listener/reader. Listener/ reader which is touched his/her feeling will smile and laugh. One of discourses which contain humor is found in Djaka Lodang magazine in Semarangan rubric. This Semarangan rubric is realized in discourse which describe the people’s daily life. This daily life is the activity which is described in narrative and in picture story. Data sources of this research is discourse of Semarangan rubric found in Djaka Lodang number 15,14,11,10 dan 9 in 2015. Data analized is picture illustration found in coloum of Semarangan rubric. The data analized technique used is content analysis. Based on the result of analysis, The humor writers use many aspect of language as a resource of creativity in which one of the creativities is language deviation which means the deviation from something expected. This deviation aims to create something funny so that the readers can be entertained. Meanwhile the aims of speech in Semarangan rubric are giving order, asking, giving information, and quipping. Key words: humor, Djaka Lodang